Macroeconomic variables that influence Shariah Index: case of Malaysia market / Muhammad Adly Zakaria - Zakaria, Muhammad Adly (Faculty of Business and Management, 2011)
This research is study about factor that influence Shariah Index in Malaysia market. Shariah Index is index that is similar to composite index. The differences between Shariah Index and composite index is the Shariah Index is based on Islamic law. Microeconomic variables such as Foreign Exchange, interest rate and inflation are the variables that always effect in investment sector. The investor always study about these variables to know the impact of this variables while making investment especially in Shariah Index. As a result, this study tries to examine the relationship between the Shariah Index and foreign exchange, inflation and interst rate. Multiple Linear regression was used to get the finding, which is the result of relationship between Shariah Index and interest rate, inflation and foreign exchange. The result show uncertainty relationship between this dependent variable which is Shariah Index and independent variables which is foreign exchange, inflation and interest rate. But. Some of the finding has constant with the previous research. The finding that I have got through this research is all the microeconomic variables, which is foreign exchange, interest rate and inflation has negative relationship. Further insight, the result perhaps can help the investor to make a right decision while doing investment in Shariah Index.